جودة الحياة الوظيفية وأثرها على الالتزام الوظيفي لدى العاملين في المؤسسة الاقتصادية - دراسة حالة مؤسسة ورود للروائح والعطور بالوادي - لطفي, عاشور; خالد, بن خليفة; مراد, شريفي (University of eloued جامعة الوادي, 2021)
هدفت هذه الدراسة إلى التعرف على جودة الحياة الوظيفية وأثرها على الالتزام الوظيفي لدى العاملين في مؤسسة وورود لصناعة الروائح والعطور بالوادي، وقد تم الاعتماد على المنهج الوصفي في هذه الدراسة، حيث تم تصميم استبانة كوسيلة لجمع البيانات والتي وزعت على عينة مكونة من كل عمال المؤسسة محل الدراسة مستخدمين بذلك طريقة العينة الشاملة ، والذي بلغ عددهم (103) مفردة، واسترد منها (100) استبانة صالحة للتحليل الإحصائي ، ولمعالجة وتحليل هذه البيانات تم الاعتماد على البرنامج الإحصائي (SPSS.V26)، توصلت الدراسة إلى عدة نتائج أهمها توفر جودة الحياة الوظيفية من وجه نظر العاملين بدرجة متوسطة، وتم التوصل إلى وجود علاقة ذات دلالة إحصائية عند مستوى الدلالة 0.05 ≥ α بين أبعاد جودة الحياة الوظيفية ومستوى الالتزام الوظيفي، وتبين أيضا أن كل من بعدي التدريب والتعلم، الأمن والاستقرار الوظيفي كان لهما تأثيرا فعالا على مستوى الالتزام الوظيفي في مؤسسة وورود لصناعة الروائح والعطور بالوادي." The study aimed to identify the quality of work life and impact on the organizational commitment of the employees of Wouroud company for the manufacture of scents and perfumes – El Oued, this study was relied in The descriptive method where a questionnaire was designed as a mean of data collection, which was distributed to a sample made up of all the workers of the institution using the comprehensive scanning and sampling method. The resolutions are (103) , (100) questionnaires valid for statistical analysis were retrieved. To process and analyze this data, the statistical program (SPSS.V26) was relied on; The study reached several results, the most important of which is the availability of the quality of career life from the point of view of the workers to a moderate degree according to the research scale. The study reached several results, the most important of which is the quality of work life from the point of view of the workers to a moderate degree, And it was found that there is a statistical significant relationship at the significance level (α ≥ 0.05) between the dimensions of quality of work life and the level of organizational commitment. Also found that both the training and learning dimensions, security and job stability had an effective impact on the level of job commitment in Wouroud Foundation for the manufacture of scents and perfumes – El Oued"
ماستر ادارة اعمال
Keywords: جودة الحياة الوظيفية، الالتزام الوظيفي، مؤسسة وورود لصناعة الروائح والعطور بالوادي.; Quality of work life, organizational commitment, Wouroud campany for the manufacture of scents and perfumes.